Recent Publications (Quarterly Journal of Economics, 1956)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 70, Issue 1, February 1956, Pages 167–168, https://doi.org/10.1093/qje/70.1.167 Published: 01 February 1956